Utvärdering och analys av det trådlösa nätverket på företagsbyarna Acusticum och Furunäset - Conrad, Marcus (2015)
This report contains measurements and analyses of the municipal wireless network at two businesses parks in Piteå, Furunäset and Acusticum. Piteå Näringsfastigheter AB (PNF), thecompany I made this report for, wanted to know about the current wireless coverage offered by the municipal network at the previously mentioned businesses parks that they take care of. I was also tasked to come up with ideas how you could improve them. In the existing municipal network at Furunäset there were seven different accesspoints and nine more at Acusticum.The focus of this report will be on what can be improved or changed but also a potential expansion of the current networks. It will deal with whether or not it is a good idea to have an open and unprotected wireless network to begin with.Contents of the report :• Present and future wireless technology.• "Heatmaps" over the present wireless coverage at the two businesses parks• Suggestions and discussion about changes/improvements of the network.• Open Wi-Fi and network security. Validerat; 20150326 (global_studentproject_submitter)